Comparison of Ketoprofen Phonophoresis with Ketoprofen and Lidocaine- Prilocaine Phonophoresis in Patients with Subacromial Impingement Syndrome - Hayal Güler; Ayşe Dicle Turhanoğlu; Kerem İnanoğlu and Deniz İnanoğlu and Cahit Özer (Archives of Rheumatology, 2009)
Objective: The aim of the present study was to compare ketoprofen phonophoresis with ketoprofen and lidocaineprilocaine phonophoresis in patients with subacromial impingement syndrome (SIS). Material and Methods: Seventy patients (39 female, 31 male) with SIS were included in this study. The patients were divided into two groups and a 15-session physical therapy and rehabilitation program was performed in each group. Ketoprofen and lidocaineprilocaine phonophoresis were performed in the first group and ketoprofen phonophoresis alone in the second group. Hot pack, transcutaneous electrical nerve stimulation (TENS) and exercises were applied in all patients. Severity of shoulder pain was determined by visual analogue scale (VAS). Range of motion (ROM) was measured by goniometer. Functional capacity of patients was evaluated by UCLA (The University of California-Los Angeles) score. All of the measurements were performed before treatment and in the 1st and 3rd months after treatment. Results: There was no significant difference between the two groups in VAS and UCLA scores before treatment initiation (p>0.05). VAS scores of Group 1 were lower than of Group 2 (p=0.020) in the 3rd month follow-up. ROMs and flexion, abduction and internal rotation were higher in Group 2 than Group 1 (p=0.009, p=0.001, p=0.019, respectively) before treatment. Abduction measurements in Group 2 were higher than in Group 1 in the 1st month after treatment (p=0.024). However, there was no significant difference between the two groups in UCLA and ROM values in the 3rd month (p>0.05). There was also no significant difference between the two groups in external rotation values before and after treatment (p>0.05). Conclusion: Our study showed that ketoprofen and lidocaineprilocaine phonophoresis were more effective on pain and ROM than ketoprofen phonophoresis alone in the 3rd month after treatment in patients with SIS. (Turk J Rheumatol 2009; 24: 88-93)